Media and political agenda setting: the case of mental health policy in Lithuania - Šumskienė, Eglė; Šumskas, Gintaras; Mataitytė-Diržienė, Jurga; Pūras, Dainius; Karaliūnienė, Rūta (Socialinė teorija, empirija, politika ir praktika, 2017)
Media has a very specific role in forming agenda of mental health policy. In their reports, journalists directly question systemic issues, trajectories of the mental health policy and respective legislation. Media also acts as a mediator between citizens and politicians rendering understanding to the latter that their electorate is scared and supports increasing means of guardianship and control. Finally, media can ignore important outcomes of mental health policy. This strategy gives an account that mental health issues are of low importance and public scrutiny is not needed. The data for the context and content analysis derived from two main sources: online news webpage (time frame covers year 2000–2011, 1353 cases) and Parliament records of official proceedings (year 1990–2010, 567 cases). Media discourse proved to have a significant influence on political agenda, since in most cases political discussions on the topic of mental health were referred to media sources. Research data suggests that media coverage as well as the political debates on mental health are characterised by general stagnation, superficial understanding and stereotypical attitudes. This overall pattern was breached during the period of 2004–2006 which was marked by significant international events, namely the EU entrance and adoption of the Mental Health Declaration for Europe. During this period the policy of mental health received considerable attention in the media, decreased media articles related to criminalisation of mental health. The research identified major players that were able to break the vicious circle in the media and political discourse around the marginalised and stigmatised subject.